PROBLEMS OF MOBILIZING THE COMPETENCES OF FUTURE MEDICALSPECIALISTS - A.K.Jamolov (Western European Studies, 2025)
This  article  analyzes  the  mobilization  of  professional  competencies  of  future medical  professionals  as  a  pedagogical  issue.  In  the  context  of  constant  changes  and innovations in modern medicine, it is crucial to develop specialists’ knowledge, skills, andqualifications  in  a  flexible  manner.  The  process  of  mobilizing  competencies,  i.e.,  directing them toward rapid and effective application, requires significant methodological approaches in the  medical  education  system.  The  article  highlights  the  pedagogical  foundations  of  this process,  the  role  of  educational  technologies,  and  the  importance  of  utilizing  innovative methods.  Additionally,  it  examines  the  factors  hindering  the  mobilization  of  professional competencies among medical professionals and explores ways to overcome them
Keywords: Medical education; professional competency; mobilization